Bread without wheat flour - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The aim of the Broci project in Cote d'lvoire is to promote the processing of tropical staples (cereals, roots and oilseeds) into a wide range of breads, biscuits and cakes known as bros. This generic term implies that the proportion of wheat flour...